AUTOMATION OF INVENTORY PROCESS OF PERSONAL COMPUTERS - A. I. Zaharenko; A. V. Vashetin (Литьë и металлургия)
The modern information infrastructure of a large or medium-sized enterprise is inconceivable without an effective system of the computer equipment and fictitious assets inventory. An example of creation of such system which is simple for implementation and has low cost of possession is considered in this article.